SnO2 thin films - chemical vapor deposition and characterization - Lu, Yinmei; Justus Liebig University Giessen (My University, 2015)
This thesis work demonstrates that CVD has an excellent potential as a growth technique for high-quality SnO2 epitaxial thin films. We have attempted to use SnI2 (Sn2+) as Sn precursor. All films consisted of pure-phase SnO2 with a rutile structure. In this work we have tried to use quartz glass, c-, r-, and a-plane sapphire as substrates. To optimize the deposition process, we investigated systematically the influence of the CVD parameters on the film properties, such as the substrate temperature, the precursor SnI2 evaporation, and the oxygen flow rate, etc. A series of epitaxial SnO2 films were obtained on c-plane sapphire. The films on c-sapphire show an epitaxial relationship with the substrate of SnO2 (100)//Al2O3 (001) (out-of-plane) and SnO2[010]//Al2O3<110> (in-plane). Detailed analysis using XRD and SEM reveal that the crystal quality and the morphology of SnO2 films are dependent on the O2 flow rate during film deposition, which is very likely caused by a variation of the VO density in the films. This series of experiments indicates that the quality of SnO2 films is enhanced with increasing O2 gas flow rate up to 40 sccm, and then declines with further increase of the O2 flow rate. As the O2 flow rate is increased, the carrier concentration in films decreases. This indicates a decrease of the VO concentration with increasing O2 flow rate during the film growth. The epitaxial SnO2 film on c-sapphire starts in the Volmer-Weber growth mode. The films initially grow by the nucleation of discrete islands with rectangular unit cells of c = 3.187 (relaxed) and b = 4.759 Å (strained) in-plane. There are three possible orientations of the unit cell of the SnO2 islands with respect to the c-sapphire substrate. The orientations are rotated by 120° with respect to each other. At a characteristic layer thickness of about 50 nm the islands begin to merge, leading to a closed SnO2 film growth on c-sapphire with a characteristic domain structure. The films grown on r-plane sapphire substrates also consist of pure-phase SnO2. The epitaxial relationship of the films with the substrate is SnO2(101)//Al2O3(012) out-of-plane, SnO2[010]//Al2O3[100] in-plane. The absolute average transmittance of the films is more than 85% in the visible and infrared range. The optical absorption edge is in the range of 3.57 to 3.78 eV in this study. High-quality heteroepitaxial SnO2 films can be obtained at a high substrate temperature of 900 °C by CVD. The growth rate of these films on sapphire is about 2 µm/h. XRD measurements determined the FWHM of rocking curve of SnO2 (200) reflection for the film with thickness of 3.5 µm on c-sapphire to be only 0.04°, indicating the high degree of out-of-plane ordering of this film. The domains of these films are huge and possess diameters of more than 30 µm. Angle-dependent Raman spectra for SnO2 (101) on r-sapphire is in good agreement with the calculated scattering intensities of the phonon modes A1g, B2g and Eg. The low temperature (67 K) PL and TRPL spectra exhibit an excitonic emission located at about 3.3 eV, whose energy slightly varies with the time after pulsed excitation. A broad deep-level emission is located at 2.6 eV, which is probably caused by the formation of trapped states due to oxygen vacancies. The absolute average transmittance of the films on sapphires is above 90% in the visible and infrared range. An optical absorption edge of 3.74 eV for these thick films on sapphire substrates is estimated.The success of epitaxial growth of SnO2 films on c- and r-sapphires indicates that heteroepitaxy may not only occur in material systems with similar structural symmetry, e.g. cubic on cubic, tetragonal on cubic, or vice versa, but is also possible for materials with different symmetry, e.g., tetragonal on hexagonal. Epitaxial growth of SnO2 on sapphire has been demonstrated by various deposition techniques, such as CVD, MBE, sputter deposition and PLD etc. The best results have been obtained on r-sapphire substrates. This is in agreement with the findings of this thesis for CVD growth. Thus, the foundation is laid for obtaining high quality SnO2 films which can be used in fundamental studies of the properties of this material system. Research directions based on the findings reported here may concern the open questions of controlled extrinsic doping of SnO2 or of improvement of the SnO2 films by employing sputtered SnO2 buffer layers. Both are issues, which need to be addressed on the road towards SnO2 devices.
SnO2 dünne Schichten Chemische Gasphasenabscheidung (CVD) und Charakterisierung
Keywords: ddc:530